Lebanese Women and Literature - Aghacy, Samira (1997)
Since we are dealing with texts written by women, the question that comes to mind is whether or not there is a unique or particular way in which women inscribe representation. My examination of texts written by women as well as men from the 1950's to the present reveal that no clearcut or categorical differences occur between texts written by men and those written by women. There seems to be no difference in the language they use or the techniques employed in their writing. Is it a question of content then which makes texts written by women different?